SOCIAL INDICATORS OF THE QUALITY OF LIFE OF THE POPULATION POPULATION GROWTH DYNAMICS: PROBLEM AND SOLUTION (International journal of artificial intelligence, 2024)
The article analyzes the dynamics of population growth and its national composition in the era of rapid scientific and technological development. In both cases, whether the world's population is increasing or decreasing, countries around the world find it appropriate to test mechanisms to improve the quality of life of the population in practice.The fact that the population of developed or developing countries today has a higher or better quality of life is substantiated on the basis of scientific facts.